Changing the Way That Math is Taught: Conceptual Versus Procedural Knowledge (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
The purpose of this article is to present teachers with information and data regarding the relationship that exists between procedural and conceptual knowledge while attempting to validate the notion that the development of conceptual knowledge should be at the forefront of student learning in the mathematics classroom. The article first delves into the definitions and overall significance that each of these modalities have in the mathematics classroom and after doing so, the article examines the theoretical ideologies that encompass them. The article concludes with a look into how the two knowledge bases are related, as well as empirical evidence regarding which is better for effective classroom instruction.